The influence of Free and Open-Source Software-Geographic Information System online training on spatial habits, knowledge and skills - Ismail, Arif; Millary Agung, Widiawaty; Jupri, Jupri; Setiawan, Iwan; Sugito, Nanin Trianawati; Moh. Dede, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The era of regional autonomy after the 1998 reformation prompted the formation of a new formal administrative area in Indonesia as an effort to encourage the national development. Pangandaran Regency, after divided from Ciamis Regency, requires attention from higher education stakeholders in the spatial field to manage its natural and social-economic resources. Free and Open-Source Software-Geographic Information System (FOSS-GIS) training is the appropriate solution through the community service and empowerment program from university. This study aims to determine the effect of FOSS-GIS training on spatial habits, spatial knowledge, and spatial skills. The online training was attended by 24 participants who are officials from the government of Pangandaran Regency. To determine the effect, we used Wilcoxon's Test and Paired Sample T-Test on spatial habits and spatial knowledge. We analyzed the spatial skills of self-paced tasks and presentation of results by the participants. This study shows a positive effect of FOSS-GIS training which can be seen from the increase in scores between pre-test and post-test. The spatial habits increased 5.4 percent, whereas the spatial knowledge increased 6.1 percent. Participants were also able to demonstrate all their spatial skills to make a tsunami hazard map and present it. FOSS-GIS online training is effective for improving spatial habits, spatial knowledge, and spatial skills for participants in any background.